2021
DOI: 10.1007/s00521-021-06384-x
|View full text |Cite
|
Sign up to set email alerts
|

An adaptive backpropagation algorithm for long-term electricity load forecasting

Abstract: Artificial Neural Networks (ANNs) have been widely used to determine future demand for power in the short, medium, and long terms. However, research has identified that ANNs could cause inaccurate predictions of load when used for long-term forecasting. This inaccuracy is attributed to insufficient training data and increased accumulated errors, especially in long-term estimations. This study develops an improved ANN model with an Adaptive Backpropagation Algorithm (ABPA) for best practice in the forecasting l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Each layer structure is calculated according to the framework of RNN. According to the parameter sharing nature of RNN, the gradient of the weight is the sum of all layers [27]. e loss function L operates as shown in the following equation:…”
Section: Back Propagation Through Time Back Propagation Through Time ...mentioning
confidence: 99%
“…Each layer structure is calculated according to the framework of RNN. According to the parameter sharing nature of RNN, the gradient of the weight is the sum of all layers [27]. e loss function L operates as shown in the following equation:…”
Section: Back Propagation Through Time Back Propagation Through Time ...mentioning
confidence: 99%
“…and Al-Bazi A. [31] proposed an improved ANN along with an adaptive backpropagation algorithm (ABPA) to cover the limitations of ANN and provide enhanced forecasting accuracy. The datasets comprised nine years of data attained from the ministry of electricity in Iraq.…”
Section: Adaptive Modelsmentioning
confidence: 99%
“…The ARIMA model could not detect the importance of newly introduced parameters, and the results remained more or less the same with minimal deviations. In Figure 13, (a After reviewing several proposed models for load forecasting utilizing ANN [31,33,42,44], it is concluded that ANN methods have better forecasting accuracy than statistical methods. However, in this study, we utilized ANN and other forecasting models to understand the performance and behavior of models towards feature change scenarios.…”
Section: Case Study-1 (Using Arima)mentioning
confidence: 99%
See 2 more Smart Citations